Low-Concentration As(III) Retention from Water on Polyacrylamide Modified Spent Grains - Chen1, Yunnen; Luo1, Xiaoyan; Nie1, Jinxia; Luo1, Xianping; Chai2, Liyuan (Asian Journal of Chemistry, 2014)
Human health is concerned by arsenic pollution hazards from water all around the world. The polyacrylamide with acylamino group, whose binding ability with As(III) is strong. Thus polyacrylamide was chosen as sorbent modifier for spent grains (PSGs) to treat water containing low-concentration of As(III) was studied. When PSGs is 5 g/L, initial concentration of As(III) 0.1 mg/L, the equilibrium can be attained after 1.5 h. The As(III) sorption by PSGs had a better relevance to Freundlich isotherm than Langmuir isotherm. Thermodynamics study showed that As(III) retention with PSGs is the exothermic and spontaneous. The co-existing anions of F-, SO42- and PO43- can inhibit the As(III) retention. Headwaters containing 0.07 mg/L As(III) can be reduce to 0.01 mg/L after treated by 1.5 g/L PSGs, which meet the provisional guideline value of WHO for arsenic in drinking water.